CEDAW indicators for South Asia an initiative - UNIFEM South Asia Regional Office, New Delhi; CENWOR (Organization : Sri Lanka). (New Delhi UNIFEM, South Asia Regional Office, 2004)
Study on CEDAW with reference to South Asia conducted by CENWOR.
"Supported by UNIFEM, South Asia Regional Office."
"CEDAW, Convention on the Elimination of All Forms of Discrimination against Women"--Cover.
Keywords: Sex discrimination against women -- South Asia; Sex discrimination against women -- Law and legislation -- South Asia